Acerca de la complejidad social y sus referentes en el escenario del bajo río San Jorge (Caribe colombiano) (2008)
ABSTRACT: This article is by way of an introductory and its main objective is to present some concepts related to the processes of social complexity, as well as their subsequent implementation in the lower region of the San Jorge River from the Northwestern Colombian Caribbean zone. It specifically deals with the relationship between the issues of environmental modification and the processes towards political centralization. Under such an assumption, an approximation to the interpretation of the past in the region is suggested; in order to both critique and rethink monolithic approaches which are used to address the social organization of groups settled in the Depresión Momposina.